Incidental Learning and Long‐Term Retention of New Word Meanings From Stories: The Effect of Number of Exposures. Issue 1 (27th August 2018) - Hulme, Rachael C.; Barsky, Daria; Rodd, Jennifer M.
Abstract : This study used a Web‐based naturalistic story‐reading paradigm to investigate the impact of number of exposures on incidental acquisition and long‐term retention of new meanings for known words by native English‐speaking adults. Participants read one of four custom written stories in which they encountered novel meanings (e.g., a safe concealed within a piece of furniture) for familiar words ( foam ). These meanings appeared two, four, six, or eight times in the narrative. Results showed reasonably good memory of the new meanings, assessed by cued recall of novel meanings and word forms, after only two exposures, emphasizing the importance of initial encounters. Accuracy in cued recall of novel meanings showed a linear, incremental increase with more exposures. There was no significant forgetting after 1 week, regardless of the number of exposures during training, demonstrating the efficiency with which adults acquire new word meanings incidentally through reading and retain them over time. Open Practices: This article has been awarded an Open Data badge. All data and analysis scripts are publicly accessible via the Open Science Framework athttps://osf.io/ybu6r . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .